Social Capital as a Strategy for Economic Recovery of Tourism Actors in the Lok Baintan Floating Market Post-Flood in the New Normal Era - Rahmini, Noor; Rahayu, Dewi; Fauzan, M. Ervan; Wibowo, Chahyo Agung (Budapest International Research and Critics University, 2021)
This research is qualitative. This research focuses on finding and identifying the form of social capital that exists in Lok Baintan Village through the interaction of economic actors in the Lok Baintan Floating Market. Social capital is also seen in how social capital is used to reduce the impact of floods—using in-depth interview techniques, field observations, and documentation—data analysis through data reduction, data presentation, conclusion drawing/verification, and credibility. The research shows that the form of social capital of the Lok Baintan Village community consists of trust, networks, and norms. Community trust in religion, government, volunteers, and community members is relatively high NetworkNetwork is formed from inside and outside the community, values and norms are still being implemented by the community, namely Bepanduk, bubuhan, gawi sabumi, and baakuran.